Cost-utility analysis of a polylactic acid matrix versus a collagen dressing for the closure of diabetic foot ulcers - Khorasani, Elaheh; Batra, Aashita; Bartlett, Robert; Bergquist, Stephen; Liden, Brock A.; Rangel-Berridi, Karla (Frontiers in Public Health, 2025)
BackgroundDiabetic foot ulcers (DFUs) are a common and serious complication of diabetes, often requiring the use of advanced care products, which may have high upfront costs. With the hypothesis that this approach leads to faster healing, reduced costs, and better quality-adjusted life years (QALY), this study evaluates the economic outcomes, including cost-effectiveness and cost–benefit, of an alloplastic polylactic acid (PLA) dermal matrix and compares it to collagen dressings in managing DFUs.MethodsThis cost-utility analysis was based on a randomized controlled trial involving patients with DFUs treated with either PLA matrices or collagen dressings, alongside standard wound care. Data on wound healing, cost of care, and QALY were collected over the whole duration of the trial (31-week period). We conducted a cost–benefit analysis by quantifying the monetary impact of reduced time-to-heal and avoided healthcare utilization. Additionally, we performed a cost-utility analysis using QALYs to capture patient-centered benefits.ResultsAt 12 weeks, 90% of the PLA group achieved wound closure compared to 30% in the collagen group, with PLA matrices reducing healing time by 44%. The cumulative cost of treatment for PLA was significantly lower, averaging 2,928 compared to 5,542 for collagen dressings (p < 0.001). Sensitivity analyses confirmed the cost-effectiveness of PLA even when home healthcare costs were excluded. Cost–benefit analysis also demonstrated higher QALY in the PLA treated group.ConclusionPLA dermal matrices provide a cost-effective alternative to collagen dressings, promoting faster wound closure, improved quality of life, and reduced healthcare costs. These results support the adoption of PLA as a preferred treatment for DFUs.